Theoretical Analysis of Invariant, Subinvariant and Variative Components of Inorganic Substance Properties (Eurasian Scientific Herald, 2023)
Theoretical analysis of invariant, subinvariant and variative components of the properties of inorganic matter, the article considers these principles.